Perancangan Dinamometer untuk Mengukur Gaya Potong pada Mesin Freis untuk Pemesinan Material Fiber Reinforced Polymer - Firman Ridwan; Refki Harvendri (Metal: Jurnal Sistem Mekanik dan Termal, 2020)
Milling machine is a machine that cuts a workpiece using a plural chisel that rotates on a freis machine. During the freis process, the material is cut because of the cutting force that occurs between the tool and the workpiece. The amount of cutting force can be known by theoretical calculations, but the theoretical calculation will produce a less accurate cutting force because of the many factors that influence the cutting force and the assumptions given in the calculation. Therefore, direct measurements are needed in order to see the magnitude of the cutting force that occurs during the freis process. The amount of cutting force obtained will be needed in analyzing machining parameters to obtain a combination of machining that is efficient and profitable. The tool used to measure the amount of cutting force on a freis machine is a dynamometer. The constituent components of the dynamometer are loadcell strain gauge, INA 125P amplifier IC, and national instrument hardware acquisition data 6212. The dynamometer is designed to be able to read 3 directions of force, namely the cutting force (Ft), axial force (Fz), and feeding force (Fy). Measuring the average cutting force (Ftm) obtained using aluminum workpieces is 97,6002 N, acrylic workpiece is 65,3338 N, GFRP (Glass Fiber reinforce polymer) chopped strand mat is 146,8845 N, and GFRP woven roving is 103.3915 N. Dimensions of the dynamometer are designed with a total length of 32 cm, width 32 cm, and height of 18 cm.